Bemerkungen zur Synthese von 2-Nitrotoluol-6-sulfonsäure und 2-Aminotoluol-6-sulfonsäure - Alfred Courtin (CHIMIA)
2-Aminotoluene-6-sulfonic-acid (1) was prepared by the reduction of 2-nitrotoluene-6-sulfonic-acid (2). The precursor of 2, 2-nitrotoluene- 6-sulfonylchloride (16), was synthesized from 2-amino-6-nitro-toluene (13) directly, by diazotization followed by reaction with SO2/CuCl2 and, indirectly, via diazotization and substitution to 2-nitro-6-thiocyanotoluene (14), followed successivly by reductive dimerization to the disulfide 15 and oxidative chlorination.